2016
DOI: 10.1007/s10549-016-4088-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to delays in diagnosis of breast cancers in Ghana, West Africa

Abstract: Background Late diagnoses and poor prognoses of breast cancer are common throughout Africa. Methods To identify responsible factors, we utilized data from a population-based case-control study involving 1,184 women with breast malignancies conducted in three hospitals in Accra and Kumasi, Ghana. Interviews focused on potential breast cancer risk factors as well as factors that might contribute to presentation delays. We calculated odds ratios (OR) and 95% confidence intervals (CI) comparing malignances with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 25 publications
6
60
0
Order By: Relevance
“…Many of these findings are consistent with previous work in SSA. Low levels of education have, not surprisingly, been found to be associated with advanced stage BC in many studies in the region . Long delays between first symptom recognition and diagnosis are also consistent with previous SSA research, and were associated with more visits to health care provider facilities .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Many of these findings are consistent with previous work in SSA. Low levels of education have, not surprisingly, been found to be associated with advanced stage BC in many studies in the region . Long delays between first symptom recognition and diagnosis are also consistent with previous SSA research, and were associated with more visits to health care provider facilities .…”
Section: Discussionsupporting
confidence: 85%
“…Low levels of education have, not surprisingly, been found to be associated with advanced stage BC in many studies in the region. [24][25][26] Long delays between first symptom recognition and diagnosis are also consistent with previous SSA research, 24 and were associated with more visits to health care provider facilities. 25 Reducing delays to three months is a reasonable target in SSA, as it is difficult to show any worsening of outcome when treatment is initiated after that time; delays longer than one year should be considered extreme in any system.…”
Section: Comparisons With Other Studiessupporting
confidence: 86%
See 1 more Smart Citation
“…Prior studies have identified patient and system factors associated with late presentation among breast cancer patients in SSA [11]. The largest study conducted in Ghana identified low level of education and delayed care-seeking behavior as risk factors for presenting with tumors larger than 5 cm [8]. Similarly, other smaller studies have identified limited knowledge [11][12][13][14][15][16], stigma associated with a cancer diagnosis, lack of social and financial support, and seeking alternative treatment from traditional healers as risk factors for delayed presentation [11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…16 A significant proportion of breast biopsies for palpable masses in a large cohort of breast cases in Ghana and a retrospective analysis of breast presentations in Rwanda was benign. 9,16 Thus, it is unethical and unsafe to offer mastectomy, cytotoxic chemotherapy, or other systemic therapy to a woman without having a pathologically confirmed diagnosis of breast cancer at the onset, and optimal treatment depends on the elucidation of both the stage of disease and the biologic markers, hormone receptors, and Human epidermal growth factor receptor 2 (HER2).…”
Section: Introductionmentioning
confidence: 99%